2002
DOI: 10.1097/00000374-200207000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Stress Response Caused by Chronic Alcohol Intake in Aged Rat Brain

Abstract: Chronic alcohol intake causes a stress response in the aged rat brain. It is thought that the increased level of Hsc70 is brought about by an increase of denatured proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…The oxidative stress marker Hsp70 was demonstrated to have augmented release from neurons when exposed to HIV-1 with CD4-positive cell lines and macrophages (15,36,37). The results are also in agreement with other studies that have shown that EtOH can increase the expression of transcription factors (66) and the secretion of heat shock proteins in alcohol-exposed tissue (62,80,94).…”
Section: Coculturing Of Infected T Cells With Neurons or Neurons Exposupporting
confidence: 88%
“…The oxidative stress marker Hsp70 was demonstrated to have augmented release from neurons when exposed to HIV-1 with CD4-positive cell lines and macrophages (15,36,37). The results are also in agreement with other studies that have shown that EtOH can increase the expression of transcription factors (66) and the secretion of heat shock proteins in alcohol-exposed tissue (62,80,94).…”
Section: Coculturing Of Infected T Cells With Neurons or Neurons Exposupporting
confidence: 88%
“…Hsp70 participates in translation, protein translocation, proteolysis and protein folding, suppressing aggregation and reactivating denatured proteins [33]. When we exposed primary astrocyte cell cultures to ethanol, we observed a significant increase in Hsp70 content in the cells, supporting previous studies [13,34,35]. Interestingly, changes in the Hsp70 expression were smaller in those cells previously enriched with vit-C before being exposed to ethanol, indicating that cells were able to cope better with the ethanol-induced insult.…”
Section: Discussionsupporting
confidence: 85%
“…Other proteins, such as several HSP70s, showed an alcoholism‐induced shift from one isoform to another. Most HSP70 expression is stress‐induced 40, and different HSP70s are induced by short‐term 41–43 and long‐term 14, 15, 44, 45 alcohol consumption; however, some are also expressed at a basal level ( e.g . in human brain HSP70‐2 46, HSP70‐5 47 and HSP70‐8 48, 49).…”
Section: Discussionmentioning
confidence: 99%